A case of gastric and duodenal mucosa-associated lymphoid tissue lymphoma with multiple gastric cancers: a case report - Takashi Yokoyama; Tetsuya Tanaka; Suzuka Harada; Takeshi Ueda; Goki Ejiri; Shoh Sasaki; Maiko Takeda; Atsushi Yoshimura (Surgical Case Reports)
Abstract Background Gastric mucosa-associated lymphoid tissue (MALT) lymphoma is often caused by Helicobacter pylori and has a good prognosis. Rarely, patients with MALT lymphoma may have gastric cancer and have a poor prognosis. Case presentation We herein report a case in which surgical treatment was achieved for a 72-year-old male patient with gastric and duodenal MALT lymphoma coexisting multiple gastric cancers. He underwent upper endoscopy for epigastric discomfort, which revealed mucosal erosion on the posterior wall of the middle body of the stomach, an elevated lesion on the duodenal bulb, and a raised tumor on the antrum of the stomach. He was diagnosed with gastric and duodenal MALT lymphoma with early gastric cancer. One month after H. pylori eradication, a second upper endoscopy revealed no improvement in the gastric or duodenal mucosa, and areas of strong redness with a shallow recess just below the cardia of the stomach. As a result, a diagnosis of gastric and duodenal MALT lymphoma with two gastric cancers was made. Total gastrectomy with proximal duodenum resection using intraoperative upper endoscopy and regional lymph node dissection was performed. Pathologically, gastric and duodenal MALT lymphoma and three gastric cancers were detected. Since one of them was an advanced cancer, he started taking S-1 after his general condition improved. Conclusion For early detection of gastric and duodenal MALT lymphoma or gastric cancer, appropriate upper endoscopy and a biopsy are important. It is necessary to select a suitable treatment, such as H. pylori eradication, endoscopic treatment, surgery, chemotherapy, and irradiation, according to the disease state.